Cydonia oblonga M., A Medicinal Plant Rich in Phytonutrients for Pharmaceuticals - Ashraf, Muhammad U.; Muhammad, Gulzar; Hussain, Muhammad A.; Bukhari, Syed N. A. (Frontiers in Pharmacology, 2016)
Cydonia oblonga M. is a medicinal plant of family Rosaceae which is used to prevent or treat several ailments such as cancer, diabetes, hepatitis, ulcer, respiratory and urinary infections, etc. Cydonia oblonga commonly known as Quince is rich in useful secondary metabolites such as phenolics, steroids, flavonoids, terpenoids, tannins, sugars, organic acids and glycosides. A wide range of pharmacological activities like antioxidant, antibacterial, antifungal, anti-inflammatory, hepatoprotective, cardiovascular, antidepressant, antidiarrheal, hypolipidemic, diuretic and hypoglycemic have been ascribed to various parts of C. oblonga. The polysaccharide mucilage, glucuronoxylan extruded from seeds of C. oblonga is used in dermal patches to heal wounds. This review focuses on detailed investigations of high-valued phytochemicals as well as pharmacological and phytomedicinal attributes of the plant.